Main presumptions of phenomenology in psychological research - Deltuva, Artūras (Psichologija, 1996)
This article discusses the border of methods of the Natural sciences in the field of Human sciences as well as the need for a new method of conducting research of consciousness and using consciousness as a tool to get knowledge instead of denying it. These ideas are discussed in connection with the ideas of E. Husserl's article “Renewal: Its Problem and Method”. The main ideas of phenomenology in connection with psychological research are presented; “What ideas are possible to accept in the practice of psychological research?” and “How can one use it practically?” Phenomenological dates are discussed as the meaning of experience, and phenomenological analysis, as an active process with the goal of giving verbal expression to the stream of human conscious experience.
Keywords: phenomenology; qualitative research; research methods